Diasporas and approaches between sex education in the initial series and confrontation to the prejudice: discussions on the municipal law "school without homophobia" of Maringá - Santos, Franciele Monique Scopetc dos; Maia, Ana Cláudia Bortolozzi (Faculdade de Ciências e Letras/Unesp, 2016)
This discussion is effective in the historical construction of the law No. 8728/2010 in Maringá, Paraná, which consolidated the fate of specific funds to the continuing education of teachers(es) of the municipal education system and allowed the first municipal program (the Brazil) to combat homophobia in basic education (early grades of schooling). We stress that Law n. 11,695 / 2010 has changed the law n. 8728/2010 of the creation the disposition to “School without Homophobia” Program. Therefore, this proposed force analysis on the discursive and descriptive plan of the training process and vote on the legislation, which from the literature, would be the only municipal law in Brazil that promotes linked to combat homophobia in the municipal project education. Like, emphasizes reflective aspects of sex education in the early grades.